Redescription of the enigmatic Thoracotropis cypriformis Freeman (Diptera, Mycetophilidae) - Oliveira,Sarah Siqueira (2012)
The Chilean species Thoracotropis cypriformis, type species of the monotypic genus Thoracotropis, is redescribed based on the only known specimen, the holotype. Habitus, head, wing venation, and male terminalia are illustrated. Comments are made on the diagnostic features of the genus and on its position in the subfamily to which it is usually assigned, the Leiinae.